2018
DOI: 10.1177/0706743718772514
|View full text |Cite
|
Sign up to set email alerts
|

Can Animal Models Inform on the Relationship between Depression and Alzheimer Disease?

Abstract: The focus on the β-amyloid (Aβ) peptide in clinical Alzheimer disease (AD) as well as in animal models of AD has perhaps biased our understanding of what contributes to the heterogeneity in disease onset and progression. Part of this heterogeneity could reflect the various neuropsychiatric risk factors that present with common symptomatology and can predispose the brain to AD-like changes. One such risk factor is depression. Animal models, particularly mouse models carrying variants of AD-related gene(s), many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 177 publications
(215 reference statements)
0
8
0
Order By: Relevance
“…We used this non-Tg model of AD to study the neurobiological links between depression and AD and the role of Aβ oligomers in the pathophysiology of amyloid-related depression, a recently identified clinical phenotype characterized by a low response to “monoaminergic antidepressants in depressed patients with an high risk to develop AD” (Li et al, 2017). Mimicking this clinical phenotype in rodents is a difficult challenge (Nyarko et al, 2019) but also an essential step to improve drug discovery processes in AD and explore the disease-modifying potential of antidepressant drugs in AD (Caraci et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We used this non-Tg model of AD to study the neurobiological links between depression and AD and the role of Aβ oligomers in the pathophysiology of amyloid-related depression, a recently identified clinical phenotype characterized by a low response to “monoaminergic antidepressants in depressed patients with an high risk to develop AD” (Li et al, 2017). Mimicking this clinical phenotype in rodents is a difficult challenge (Nyarko et al, 2019) but also an essential step to improve drug discovery processes in AD and explore the disease-modifying potential of antidepressant drugs in AD (Caraci et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The tail suspension test was used as a measure of learned helplessness and depression-like behavior, which is seen in both humans with AD (Chi et al, 2014) and mouse models (Nyarko et al, 2019), including the 3xTg-AD mice, and have been linked to impaired monoamine transmission (Romano et al, 2014). In this study, 3xTg-AD mice treated with DWG-1036 froze less frequently than the 3xTg-AD mice that received the vehicle, whereas there were no differences between the treatment groups in WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical studies have indicated that depression is a risk factor for cognitive decline and AD, while depressive symptoms manifest in 30% of patients diagnosed with AD. , Because of the association between elevated tau burden and depression, we sought to determine whether pathological tau in 5-HT neurons results in depression-like symptoms, including behavioral despair or anhedonia. 5 to 6 weeks after surgery, ePet1 hTauP301L mice and controls were subjected to tail suspension and forced swim tests.…”
Section: Resultsmentioning
confidence: 99%